Regulation and functions of RhoU and RhoV. (2nd January 2020) - Hodge, Richard G.; Ridley, Anne J.
ABSTRACT: Rho GTPases play central roles in a wide variety of cellular processes, including cytoskeletal dynamics, cell adhesion and cell polarity. RhoU and RhoV are Rho GTPases that have some atypical properties compared with classical Rho family members, such as the presence of N- and C-terminal extension regions, unusual GDP/GTP cycling and post-translational modification by palmitoylation but not prenylation. Their activity and localization is regulated by the N-terminal and C-terminal regions, and so far no GEFs or GAPs have been identified for them. Similar to Rac and Cdc42, they interact with PAK serine/threonine kinases, and in the case of PAK4, this interaction leads to RhoU protein stabilization. In cells, RhoU and RhoV alter cell shape and cell adhesion, which probably underlies some of the phenotypes reported for these proteins in vivo, for example in heart development and epithelial morphogenesis. However, the molecular basis for these functions of RhoU and RhoV remains to be characterized.